The Inhibitory Effect of Perceived Organizational Politics on Employee Voice Behavior: A Moderated Mediation Model - Liu, Qin; Zhou, Hao; Sheng, Xinyi (Frontiers in Psychology, 2021)
Research on the mediating mechanisms and boundary conditions of perceived organizational politics’ effect on employee voice is underdeveloped. Based on conservation of resources theory, we proposed a moderated mediation model in which organizational embeddedness acts as a mediator to explain why perceived organizational politics inhibits promotive and prohibitive voice. Additionally, we posited sense of impact as a boundary condition affecting this relationship. A time-lagged survey of 227 employed MBA students from a university in southwestern China revealed that organizational embeddedness mediates the relationship between perceived organizational politics and promotive and prohibitive voice, and sense of impact moderates the relationship between perceived organizational politics and promotive voice, such that the relationship is stronger when sense of impact is weaker. The moderating effect was not significant for prohibitive voice. These ﬁndings have implications for theory, practice, and further organizational research.